Reliability and Validity of Measuring the Strength of the Chin-Tuck Maneuver in Community-Dwelling Older Adults as a Means of Evaluating Swallowing-Related Muscle Strength - Naoto Kamide; Takeshi Murakami; Masataka Ando; Takuya Sawada; Wakana Hata; Miki Sakamoto (Geriatrics)
Background: The chin-tuck maneuver has been suggested to increase suprahyoid muscle activation, but a method to measure the strength of the chin-tuck maneuver has not been established. We developed a method to measure the strength of the chin-tuck maneuver (chin-tuck strength) and examined the reliability and validity of chin-tuck-strength measurement in community-dwelling older adults. Participants and Methods: The participants were 233 older adults aged ≥65 years without dysphagia or physical disability. Chin-tuck strength was measured twice consecutively using the developed device, and reproducibility was analyzed using intraclass correlation coefficients (ICCs). In addition, maximum tongue pressure, oral diadochokinesis, grip strength, knee extension strength, and the timed up and go test (TUGT) were measured as indices of swallowing-related muscle function and appendicular muscle function. The associations of chin-tuck strength with swallowing-related muscle function and appendicular muscle function were analyzed statistically. Results: The ICCs for chin-tuck strength were 0.82 (95% confidence interval [CI]: 0.73–0.88) in males and 0.87 (95% CI: 0.70–0.93) in females. Chin-tuck strength was significantly associated with maximum tongue pressure, grip strength, knee extension strength, and TUGT. Conclusions: This study suggests that chin-tuck strength is a reliable and valid assessment of swallowing-related muscle strength.